SCL/TAL1: a multifaceted regulator from blood development to disease - Porcher, C; Chagraoui, H; Kristiansen, M (American Society of Hematology, 2017)
SCL/TAL1 (stem cell leukemia/T-cell acute lymphoblastic leukemia [T-ALL] 1) is an essential transcription factor in normal and malignant hematopoiesis. It is required for specification of the blood program during development, adult hematopoietic stem cell survival and quiescence, and terminal maturation of select blood lineages. Following ectopic expression, SCL contributes to oncogenesis in T-ALL. Remarkably, SCL’s activities are all mediated through nucleation of a core quaternary protein complex (SCL:E-protein:LMO1/2 [LIM domain only 1 or 2]:LDB1 [LIM domain-binding protein 1]) and dynamic recruitment of conserved combinatorial associations of additional regulators in a lineage- and stage-specific context. The finely tuned control of SCL’s regulatory functions (lineage priming, activation, and repression of gene expression programs) provides insight into fundamental developmental and transcriptional mechanisms, and highlights mechanistic parallels between normal and oncogenic processes. Importantly, recent discoveries are paving the way to the development of innovative therapeutic opportunities in SCL+ T-ALL.